Impact of Basic Price Implementation on Production Inputs and Farming Business Income (Clumprit Village Case, Malang Regency) - Mujianto Mujianto (Universitas Muhammadiyah Sidoarjo, 2010)
The aim of this research was wanted to study about the impact of unhulled rice floor price policy (Kepres No. 2/2005) on the increase of farmers income in East java, and also study about production factors which influence paddy agribusiness income and productivity. Desa Clumprit, location of the research was one of paddy production area, in where paddy was dominant staple food crop. The research was descriptive research characterized as explanation research. Stratified Random Sampling was used to determine samples based on land used as paddy agribusiness. Data was collected by structured and unstructured survey. Secondary data was collected as Desa Clumprit, Kecamatan Pagelaran, Kabupaten Malang monograph document. Then, data was analyzed by Polynomial Linear Regression. Result of this study showed that unhulled rice floor price policy (Kepres No 2/2005) was able to increase farmer income until 18,24% from average Rp 3.438.550,- became Rp 4.072.028,- Kepres No.2/2005 did not influence paddy agribusiness productivity. After establishment of unhulled rice floor price policy, farmers income significantly influenced by seed price, land rent, and pesticides price. For larger agribusiness than 0,5 ha,decreased fertilizer and seed price, and land rent would significantly influenced paddy agribusiness income.